Nephrons and non-relapse mortality: simplified comorbidity index and acute kidney injury are associated with NRM in adults undergoing allogeneic hematopoietic cell transplant - Robinson, Clark Raymond; Habib, Alma; Klomjit, Nattawat; Cao, Qing; Holtan, Shernan Grace (Frontiers in Transplantation, 2024)
The Simplified Comorbidity Index (SCI) is a recently published 5-component, pre-transplant tool to predict non-relapse mortality (NRM) in allogeneic hematopoietic cell transplantation (alloHCT) patients. The SCI captures chronic kidney disease (CKD) using estimated glomerular filtration rate (eGFR) based on the CKD-EPI equation (KDIGO 2021 CKD-EPI), which may be more sensitive to predict risk of NRM than the creatinine cut-off in the 16-component, Hematopoietic Cell Transplant – Comorbidity Index (HCT-CI). We retrospectively assessed the ability of the SCI to risk-stratify patients and the impact of acute kidney injury (AKI) to NRM in adults who underwent alloHCT at the University of Minnesota. We included 373 patients who underwent their first alloHCT between 2015 and 2019. Through multivariate analysis, we found that patients with an SCI of greater than 4 had a higher risk of NRM. Additionally, we noted that AKIs stages 2-3 prior to day +100 was independently associated with a 3-fold greater NRM than patients who did not experience clinically significant AKI.